Effect of salat (prayer) activity on salivary status and cortisol level - Nadia Rully Auliawati; Layung Sekar Prabarayi; Rais Aliffandy Damroni; Juni Handajani (Majalah Kedokteran Gigi Indonesia, 2019)
The majority of Indonesian people are Muslim who perform the obligatory prayers five times each day known as salat. The series of activities in salat begins with wudu with a gargle movement that increases salivary secretion through mechanical stimulation. The movement of ruku and sujood when salat causes oxygen-rich blood to flow to the brain is well suited. When a person feels calmer and more psychically relaxed after performing salat and wudu, the parasympathetic nerves increase so normal cortisol levels can secrete more saliva which is aqueous with normal acidity (pH). Oral health will affect the overall health of the body. This study aimed to determine the effect of salat and wudu on the salivary flow rate, pH, and cortisol level as an indicator of oral health. The design of this study was the static group pretest and posttest design. The study was conducted by comparing the value of salivary flow rate, pH, and cortisol levels in 20 subjects consisting of 10 subjects as the treatment group and 10 subjects as the control. Saliva was collected without stimulation before and after salat activity for five minutes, followed by measurement of salivary flow rate and pH level. Salivary cortisol level was measured using Cortisol Assay Elisa kit with λ 540 nm. The results showed an increase in salivary pH, flow rate and cortisol level after the salat activity but there was no significant difference by Kruskal-Wallis test but there was a strong correlation using Kendall’s tau_b test. In conclusion, salat activity may have correlation with an increase in salivary pH, flow rate and cortisol level.